The Conceptualization Of Universal Man As The Economic Agent For Islamic Economics - Ahmad Badrun Kosasih; Mohd Mahyudi; Satria Hibatal Azizy; Shulhan Shulhan (UAS PRESS, 2026)
Along with the development of the times and the progress of Islamic economics as an alternative economic paradigm, there are fundamental problems that have not been resolved in scientific studies remain, both from the economic agent model regarding homo economicus and homo Islamicus. As the dominant model of economic agents in conventional economics and Islamic economics, each fails to represent the actual human economic behavior that occurs, creating a constant gap between theoretical idealization and empirical reality. Meanwhile, homo economicus degrades human motivation to self-interest and maximizes utility. Homo Islamicus as a model of agents is highly demanding of a high standard of behavior based on piety and which realistically cannot be observed in real economic settings. This research overcomes the gap through a qualitative approach conducting a systematic comparative literature analysis based on a three-dimensional microfundamental framework: main purpose, means, and virtues. This study argues that the concept of the 'universal man being' defined by gradual well-being as a goal, the Dominant Active Human Element (DAHE) as a means, and justice as the main virtue, are more empirically based and epistemologically coherent economic agents for Islamic economics. The findings show that the universal man being bridges the gap between theory and reality while remaining consistent with Islamic epistemological sources. Theoretically, this research provides a reconceptualized microfoundation for Islamic economics that goes beyond the limitations of both existing economic agent models, with broader relevance to heterodox economic theory and human-centered development discourse.